A formação continuada dos professores das escolas de educação básica da rede municipal de Alegrete/RS: um olhar sobre os processos de constituição da identidade profissional e docente - Leal, Vânessa Soares (2014)
This research was developed under the research line "Training, Knowledge and Professional Development" Program Graduate Education UFSM / RS, aimed to understand the processes of formation of teacher identity made possible by formative models that guide the policies of continuous formation of teachers in service, planned and carried out by the municipality of Alegrete / RS network. Our problematic research aims to understand how the actions of continuous formation of teachers in service, developed by Schools Basic Education influence the process of Constitution of teacher professional identity of participating teachers. In order to operationalize the research actions, the central problem was broken down into more specific investigative questions seeking to know: a) How to characterize the actions of continuous formation of teachers in service, promoted and developed in EEB on the municipal Alegrete / RS; b) What challenges tend to be faced by the schools for the organization and development of FC actions; c) what are the conceptions of teaching that usually guide the actions of FC; d) what aspects are considered by teachers as definers of their professional identity. We classify our research as qualitative nature. Data collection occurred through interviews with 18 teachers of the first years, 5 educational coordinators and 4 members of SMEC; as well for realization of systematic observations of formative meetings in 5 EEB, and the use of textual analysis scripts of the political-pedagogical projects of these schools, and Educational Principles and Guidelines of the Municipal Secretariat of Education and Culture. The results indicate that the actions of FC have as main reference the conceptions of educational coordinators and management teams. The formators of the actions are usually specialists or teachers of the school network. The FC occurs at school in a timely manner, following a previously established calendar. The main challenges faced by the schools in developing actions refer to the collective planning of FC; the lack of organization of actions, the disconnected thematic of the interests and needs of teachers; unpreparedness of the formators, and the participation and involvement of teachers. These challenges stem from many aspects, such as: create conditions for the teachers to participate on the meetings, which sometimes is hampered by the working hours, or even for the lack of relevance understanding of FC for the profession. As for teaching concepts that supporting the processes of FC we found in the documents and of the speech teachers, aspects consistent with the models of reflective professional and of critical intellectual who exercises your protagonism in an autonomous way in school. Already in the speech of educational coordinators noted a higher incidence of aspects which are related with the technical specialist model applying the knowledge received in the achieving the objectives proposed. Teachers and educational coordinators refer to FC as a mechanism to supply the shortcomings of the initial formation, considered insufficient in preparation for the teaching . Teachers prefer the types of FC where they can reflect about the problems of practice, with emphasis on updating knowledge, elaboration of teaching materials and the search for answers for the problems which they living in the classroom. As to the identification with teaching, the aspects considered by teachers as defining professional identity linking learning on profession to the practice in the classroom, experiences as students, to stories of life, to belonging to the group of teachers, to study, to the relationship of love and dedication to students and to teaching as a mission linking to the gift and vocation. Basically the motivations of teachers to practice a profession are focused on student learning. The biggest challenges that teachers find in the profession refer to the families participation in the school; lack of advisory services on the classroom; to overwork, and the difficulty in finding strategies that contribute on the development of students with learning difficulties. As noted in the formative meetings, the formative actions are given, in general, in a timely manner, without the effective participation of teachers in the structure. View of these facts , it seems reasonable to assert that the actions of continued formation of teachers in service, developed in some schools don't make it possible the constitution of autonomous professional and reflective identities and, yes, the constitution of identities that follow the technical model. In turn, some schools point to the formation of a greater identification with teaching, the extent that promote spaces for dialogue around the challenges and interests of teachers. In view of these observations we believe it is urgent to review the proposals for formation at the schools researched in order to provide space propulsion of investigator attitude and of the critical-reflexive practice fundamental for professional development through the formative actions collectively elaborated, giving conditions of teachers taking a reflective and autonomous professional identity.